2019
DOI: 10.21468/scipostphys.7.2.020
|View full text |Cite
|
Sign up to set email alerts
|

QuSpin: a Python package for dynamics and exact diagonalisation of quantum many body systems. Part II: bosons, fermions and higher spins

Abstract: We present a major update to QuSpin, SciPostPhys.2.1.003 -an open-source Python package for exact diagonalization and quantum dynamics of arbitrary boson, fermion and spin many-body systems, supporting the use of various (userdefined) symmetries in one and higher dimension and (imaginary) time evolution following a user-specified driving protocol. We explain how to use the new features of QuSpin using seven detailed examples of various complexity: (i) the transverse-field Ising chain and the Jordan-Wigner tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
144
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 298 publications
(149 citation statements)
references
References 112 publications
(161 reference statements)
5
144
0
Order By: Relevance
“…DS acknowledges support from the FWO as post-doctoral fellow of the Research Foundation -Flanders and CMTV. We used QuSpin for simulating the dynamics of the qubit systems [89,90]. The authors are pleased to acknowledge that the computational work reported on in this paper was performed on the Shared Computing Cluster which is administered by Boston University's Research Computing Services.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…DS acknowledges support from the FWO as post-doctoral fellow of the Research Foundation -Flanders and CMTV. We used QuSpin for simulating the dynamics of the qubit systems [89,90]. The authors are pleased to acknowledge that the computational work reported on in this paper was performed on the Shared Computing Cluster which is administered by Boston University's Research Computing Services.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…NSF PHY-1748958. We used QuSpin for simulating the dynamics of the spin systems [89,90]. The authors are pleased to acknowledge that the computational work reported on in this paper was performed on the Shared Computing Cluster which is administered by Boston University's Research Computing Services.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Acknowledgements.-It is a pleasure to thank Ehud Altman, Jorge Hirsch, Laimei Nie, and Daniel Parker for helpful discussions. Some of the quantum calculations have been performed using the QuSpin package [55,56] Appendix A: Saddle-dominated scrambling in Dicke model In this appendix, we show that saddle-dominated scrambling also takes place in the Dicke model [42,58]. Originally, it was conceived to describe N two-level atoms coupled to a single optical cavity mode.…”
mentioning
confidence: 99%